DETERMINAN FINANCIAL SUSTAINABILITY PADA PEMERINTAH DAERAH DI KABUPATEN/KOTA PROVINSI SUMATERA SELATAN - Putri, Nurhalizah Rahmah; Periansya; Dewata, Evada (Jurnal Riset Terapan Akuntansi, 2025)
This study was conducted to examine the influence of Regional Debt, Budget Solvency, and Service Solvency on Financial Sustainability in local governments in 17 districts/cities in South Sumatra Province during the period 2015–2023. This study uses secondary data sourced from Regional Government Financial Reports audited by the Supreme Audit Agency (BPK) and other statistical data, with a total of 162 observations. The analysis was conducted through a panel data regression approach with a Fixed Effect Model (FEM) using the EViews 12 application. Data processing shows that Regional Debt has a significant negative effect, indicating that increasing debt actually suppresses the region's ability to maintain fiscal desires. Conversely, Service Solvency has a significant positive effect, indicating that increasing public service capacity strengthens regional fiscal resilience. Meanwhile, Budget Solvency does not show a significant effect on fiscal sustainability. Simultaneously, the three variables provide a significant contribution to Financial Sustainability with high model strength. These findings confirm that controlled debt management, accompanied by increasing public service efficiency, is a key strategy in maintaining the financial desires of local governments in South Sumatra Province. Keywords: Financial Sustainability, Regional Debt, Budgetary Solvency, Service Solvency.